Cessie, Subrogation and Novation in Commercial Court Practices - Lilies Anisah; Rosmawati; Atika Ismail (Global Writing Academica Researching & Publishing, 2022)
In the development of bank credit, the provision of credit to the public has followed a new pattern, in which the provision of credit takes the form of an application by way of payment or transfer of rights (cessie), replacement of creditor rights (subrogation) or renewal of debt (novation) for research and writing. created and compiled using normative juridical research methods relating to subrogation, cessie and novation in bank credit. The results of this study are that the transfer or transfer of rights (cessie), replacement of creditors due to payment (subrogation) or renewal of debt (novation), are legal actions that are often carried out by banks related to credit extended to the public which are variations and patterns in credit distribution. In this case, credit facilities as the main activity of banking institutions have had the same construction since long ago, but currently the development is leading to various patterns combining technological developments with market segments and accompanying regulations.